Deposition Rates of Coal Dust in Mine Airways - R. Bhaskar; R. V. Ramani (The National Institute for Occupational Safety and Health (NIOSH), 1992)
"An airborne dust cloud is an ensemble of particles of varied size, density, shape and states of aggregation. An understanding and quantifying of the dispersion and deposition of the du.st generated in mines is essential to the development of measures for reducing worker exposure to dust.In coal mining, the major portion of the dust is generated during the cutting of coal using a shearer or a continuous miner. The major phenomenon affecting ambient concentration is the deposition of dust. Panicle deposition may take place due to the effect of gravitational, inertial, electrostatic, and thermal forces, and mechanisms such as Brownian and eddy diffusion and inenial impaction. The three major mechanisms of deposition in turbulent flow in mines are diffusion (Brownian and eddy), sedimentation and inertial impaction. The mechanisms determining panicle deposition are size dependent.From a review of the literature, there appears to be a knowledge gap in the understanding of the deposition phenomena in mine airways. In order to obtain a better understanding of the deposition of dust for various particle sizes, and to develop a set of data for evaluating predictive mathematical models/or dust flow in mines, a series of dust-flow experiments was performed under controlled conditions in mine airways. It appears that the deposition data generally follow the theoretical behavior of dust based on the combined effect of diffusional and gravitational deposition. Jn this paper, the findings of the study on the deposition of dust in mine airways and its dependence on size, velocity and concentration are discussed. A set of deposition equations that could be used to determine the approximate deposition at various points in a mine airway are presented.IntroductionThe major factor affecting ambient dust concentration in mine airways is the deposition of dust. Particle deposition may take place due to the effect of gravitational, inenial, electrostatic, and thermal forces, and mechanisms such as Brownian diffusion, eddy diffusion and inertial impaction. The major mechanisms of deposition in turbulent flow in mines are diffusion (Brownian and eddy), sedimentation and inertial impaction. Inertial impaction is significant only during changes in direction, but the change in direction of flow with resultant powerful eddies may cause increased re-entrainment of the particles, thus having a compensating effect. While the literature in aerosol sciences contain several references on deposition, most studies were done in small diameter tubes for diffusional deposition (Liu and Agarwal, 1974). The deposition data from small diameter, short tube experiments may not be applicable to studying deposition in mine airways that have large areas and extend several hundred meters. Further, the change in concentration along the length of a mine airway may significantly affect the deposition an aspect that may not be easily determined in short tubes in laboratory experiments."